Nanomaterials for Sustainable Tribology - Raina, Ankush (Taylor & Francis Group, 2023)
The text covers topics on the sustainability of nanomaterials in tribology, economic aspects of nanomaterials, theories, and mathematical models. It will serve as an ideal reference text for senior undergraduate, graduate students, researchers in diverse engineering domains including manufacturing, mechanical, aerospace, industrial, and materials